Information Technology Investment Benefit Analysis Using the Cost Benefit Analysis Method and Ranti's Generic IS/IT Business Value Method - Estiyanti, Ni Made; Wenur , Novita Ariyanti Maria; Dewi, Putri Anugrah Cahya (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The rapid development of technology affects society. The development of information technology affects the business world today. To overcome all this, companies need breakthroughs by utilizing technology, namely e-commerce. Every organization or company needs to make information technology investments to be able to ensure better performance. The purpose of this study is to find out the benefits resulting from the investment in information technology in the form of online shopping applications by one fashion retail company in Indonesia, namely PT. XYZ. Information technology investment calculation methods used in this study are the financial statement comparison analysis method, Ranti's generic IS/IT business value method, and the cost-benefit analysis method. Through calculations that have been carried out using Ranti's generic IS/IT business value method and the cost-benefit analysis method, it has been determined that the information technology investment is beneficial for the company.